Emily Hobhouse’s Psychosocial Developmental Trajectory as Anti-War Campaigner: A Levinsonian Psychobiography. - Fouché, Paul; Nortjé, Nico; Welman, Crystal; van Niekerk, Roelf (Indo-Pacific Journal of Phenomenology)
The aim of this psychobiography was to uncover, reconstruct and illustrate significant trajectories of psychosocial development and historical events over the lifespan of Emily Hobhouse (1860-1926). The British-born Hobhouse later became an anti-war campaigner and social activist who exposed the appalling conditions of the British concentration camps during the Anglo-Boer War (1899-1902), as evidenced by primary and secondary historical data. Purposive sampling was used to select Hobhouse as a significant and exemplary subject. Levinson’s four eras or seasons of lifespan development served as the theoretical psychological approach. The study was undertaken against the background of Merleau-Ponty’s ontological philosophy that elucidates a human science phenomenology where the individual cannot be separated from her social world. Alexander’s model of identifying salient biographical themes was utilized and a conceptual psycho-historical framework, based on both the life cycle theory of Levinson and significant historical periods throughout Hobhouse’s life, was employed to assist with data gathering, categorisation, and analyses. The findings highlight significant psychosocial and historical events in the life of Hobhouse that shaped her development as an anti-war campaigner. These include: The role of her strong-willed and determined mother; the denial of an opportunity to study and pursue a formal education; her management of painful feelings of abandonment and grief; the care of her father during his illness and his eventual death; the abrupt ending of her failed romantic relationship; her networking capacity; and her open-mindedness and capacity for independent humanitarian thought. Against the philosophical background of Merleau-Ponty’s phenomenological ontology, Levinson’s theory and eras proved valuable in identifying these particular psychosocial life experiences and historical events as having shaped Emily Hobhouse into an antiwar campaigner.